DIGITAL JOURNALING FOR STRESS MANAGEMENT IN INTERNATIONAL STUDENTS - Shereen Mohamed; Cahyaning Suryaningrum; Yuni Nurhamida (RADJA PUBLIKA, 2026)
International students experience different stressors in host countries, stressors related to acculturation, academic pressure, and social integration. Adversely affecting their mental health. Studies addressed the significance of coping strategies as a tool for managing stress and relieving distress feelings. This study aimed to evaluate the efficacy of a digital journaling intervention in reducing perceived stress among this population. Based on Pennebaker’s expressive writing theory, the program employed a one-week intervention using the